Modelling and Analysis Microturbine and Battery Storage System Microgrid System Based on Green Energy - Khamis, Alias; Ab. Ghani, Mohd Ruddin; Kim, Gan Chin; Mohd Aras, Mohd Shahrieel; AB Rashid, Mohd Zamzuri Bin; Dahlan, Nurfaezatul Aqma Binti (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Nowadays, many countries have shown their interest in distributed generation technology. Recently, there are many problems with the power system. One of the problems is high electricity price. The price in power generation relies largely on the type and market price of the fuel used, government subsidies, government and industry regulation, and even local climate patterns. Other than that, the usage of fossil fuel needs to be reduced as its usage results in smog and acid rain, which eventually lead to the greenhouse emission and changes in earth’s climate. To supply a better power system, this research introduces a model of MicroTurbine (MT) and battery storage MicroGrid (MG) system based on green energy. The small-scale MG is widely used in power generation system. MG can operate with renewable and non-renewable energy. Through this project, MG will be modeled by using MT as Distribution Generation (DG) and battery storage system as Distribution Storage (DS). The MG system will be simulated using MATLAB Simulink. The MG system will be analyzed in grid connected or grid-disconnected mode. The simulation shows the results of different modes of MG system. The factors and causes affecting the MG system will be discussed.